Kekerasan Terhadap Perempuan dan Rekonstruksi Budaya - Febiana Rima (Respons: Jurnal Etika Sosial, 2009)
Violence against women manifests itself in many ways in our age. It could happenin family, in school, and in society at large. Especially in patriarchal culture, violence has its rootin the doctrine that women and men are not equal. The natural differences of both wereconstructed into social relation that puts men on the highest position of power relation pyramid.Violence in this culture is an instrument to keep and protect the power of men. Searching thesolution to this social issue, this article promotes a political reconstruction that based on theuniversal declaration of human rights and political communication.